2017
DOI: 10.1007/jhep10(2017)143
|View full text |Cite
|
Sign up to set email alerts
|

Reactor fuel fraction information on the antineutrino anomaly

Abstract: Abstract:We analyzed the evolution data of the Daya Bay reactor neutrino experiment in terms of short-baseline active-sterile neutrino oscillations taking into account the theoretical uncertainties of the reactor antineutrino fluxes. We found that oscillations are disfavored at 2.6σ with respect to a suppression of the 235 U reactor antineutrino flux and at 2.5σ with respect to variations of the 235 U and 239 Pu fluxes. On the other hand, the analysis of the rates of the short-baseline reactor neutrino experim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 41 publications
(132 reference statements)
6
51
0
Order By: Relevance
“…These discontinuities are also reflected in the 235 þ 239 global fit of Ref. [42]. This discontinuity between Daya Bay evolution and global rate data sets naturally results in a higher χ (2018) yields a best-fit value of ð6.39 AE 0.10Þ × 10 −43 cm 2 =fission, nearly identical to the fit of all global rate data shown in Fig.…”
supporting
confidence: 56%
See 4 more Smart Citations
“…These discontinuities are also reflected in the 235 þ 239 global fit of Ref. [42]. This discontinuity between Daya Bay evolution and global rate data sets naturally results in a higher χ (2018) yields a best-fit value of ð6.39 AE 0.10Þ × 10 −43 cm 2 =fission, nearly identical to the fit of all global rate data shown in Fig.…”
supporting
confidence: 56%
“…On the other hand, the discontinuity could be reduced while still including all data sets. Reference [42] has shown that models including both sterile neutrinos and incorrect flux predictions provide a good fit to global IBD yield data. In addition, we have shown in this analysis that an improved combined fit is obtained by allowing incorrect …”
Section: Impact Of Variations In Experimental Parametersmentioning
confidence: 99%
See 3 more Smart Citations